ASPEK PERLINDUNGAN HUKUM HAK KEKAYAAN INTELEKTUAL (HKI) : FUNGSI SENTRA HKI DALAM PENGEMBANGAN HKI DI PERGURUAN TINGGI - Keliat, Venia Utami; Simanjuntak, Immanuel; Tarigan Sibero, Chandra Lahirisa Putra (Ilmu Hukum Prima (IHP), 2022)
The implementation of the Intellectual Property Rights (IPR) system qualitatively and quantitatively in Indonesia can be said to be still not running properly, especially in the university environment while universities are institutions that produce a lot of Intellectual Property. The low knowledge of the academic community about the Definition of IPR and the Legal Basis for IPR Protection is the main problem in this journal. This journal explains the understanding, types, and legal basis of IPR as a whole and the function of the IPR Center in the development of IPR in the Higher Education environment. The method used in this research is normative legal research, the data used in this research is secondary data and the data collection technique in this research is through library research. Keywords : Intellectual Property Rights (IPR), University, Legal Protection